(untitled) (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2020)
???? ??? ??????? ?????????? ??? ????? ??? ????? ?????? ????? ???? ??????? ?? ??? ?????? ???????? ??????? ????????? ??? ?????? ????? ???????. ???? ??????? ?????? ?????? ?? ???????. ??????? ???? ??????? ????? ????????? ???? ?????? ??? (43) ?????? ????? ??? ???? ?????? ??: ?????? ??????? (14) ?????? ?????? ????????? (7)??????? ?????? ????????? (8) ??????? ?????? ??????? (8) ??????? ?????? ??????? (6) ??????. ????? ????? ??????? ?? ???? ?????? ????? ??????? ?????? ????? ??????? ??????? ?? ??? ???????? ???????? ??????? ????? ??????? ??????? ???????? ? ?????? ????? (35) ?????. ????? ??????? ??? ??? ?????? ??? ?????? ????? ??????? ?????? ????? ???? ?????? ?? ??? ?????? ???????? ??????? ????????. ??? ????? ???????? ?? ??? ???? ?????????: ?????? ???????? ?????? ???????? ?????? ?????????? ?????? ?????????? ?????? ???????. ???? ??????? ?????? ???????? ?????? ????? ???? ?????? ?? ??? ?????? ????????? ???????? ?????? ?????? ????????? ????????? ??????? ???????. ABSTRACT The objective of this study is to know the competences of Arabic Language teachers to analyze a poetic text using structuralist Linguistic stylistic approach. The descriptive method was applied in this study. The Observation Cards used, which includes (43) competences on: the linguistic structure highlighted on (14) competences, structuralist Linguistic stylistic structure investigated (7) competences, musical structure included (8) competences, poetic image focused on (8) competences and poetic view included (6) competences. The study sample consisted of (35) teachers of grades (1 and 2) in the Secondary schools of western region, in Mecca; Saudi Arabia. The findings revealed that: The teachers own the competence to analyze poetic texts. The competences of analyzing poetic text used were: Linguistic Structure, Poetic Image, structuralist Linguistic Stylistic Structure, Musical Structure and Poetic View. The researcher recommended training for teachers to acquire the competences of analyzing poetic text by using structuralist Linguistic stylistic.